Manajemen Program Sekolah Berasrama (Boarding School) dalam Upaya Pembentukan Karakter Siswa di SMAIT Buahati Islamic School Jakarta - Muthmainnah, Venni Nabila Farah; Ahmad, Masduki; Rahmawati, Desi (Jurnal Ragam Pengabdian, 2026)
Technological advancements in the Fourth Industrial Revolution (Industry 4.0) require educational institutions to produce graduates with global competitiveness, digital competence, and strong character. This study analyzed the management of the boarding school program in developing students' character at SMAIT Buahati Islamic School Jakarta using a qualitative case study approach. Data were collected through interviews, observations, and document analysis involving school leaders, teachers, and dormitory staff, and analyzed using data reduction, data display, and conclusion drawing with source, technique, and time triangulation. The findings showed that the boarding school program was effectively managed through four management functions: planning, organizing, implementation, and evaluation. Planning was aligned with the school's vision, students' needs, Islamic values, and the Pancasila Student Profile. The program integrated academic and dormitory activities, including worship, Qur'an learning, leadership, literacy, and extracurricular activities. Continuous evaluation monitored students' behavior, discipline, and academic and non-academic performance. The program effectively strengthened students' religious character, discipline, independence, responsibility, leadership, and social awareness.